(untitled) (Bangladesh Journal of Otorhinolaryngology, 2011)
Dermoid cysts are benign congenital lesions usually presenting as midline neck mass. They rarely appear in the lateral neck region. There is a report of dermoid cyst along with an isolated loop of intestine presenting as lateral neck swelling in a 10-year-old boy. The intestinal loop was completely separated from the pharynx and full of muconeum was found after opening the loop. Complete excision was done. After a thorough search, we conclude that this is the first reported case of neck teratoma presenting as loop of intestine. Key words: Dermoid; Teratoma; Primitive loop of intestine. DOI: 10.3329/bjo.v16i2.6850 Bangladesh J Otorhinolaryngol 2010; 16(2): 133-135